2017
DOI: 10.5194/hess-2017-560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topography significantly influencing low flows in snow-dominated watersheds

Abstract: and other environmental fields. Flow variables include annual mean flow (Qmean), Q10%, Q25%, Q50%, Q75%, Q90%, and annual minimum flow (Qmin), where Qx% is defined as flows that at the percentage (x) occurred in any given year. Factor analysis (FA) was first adopted to exclude some redundant or repetitive TIs. Then, stepwise regression models were employed to quantify the relative contributions of TIs to each flow variable in each year. Our results show that topography plays a more important 30 role in low flo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…The difference in the drought progression processes between areas with different landscapes was also found by Sadri et al (2016) in the eastern United States. This confirms the findings of Laaha et al (2017), Bormann and Pinter (2017) and Li et al (2018) that the importance of local environmental elements on the process of formation of streamflow droughts is of greater importance than general global factors.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…The difference in the drought progression processes between areas with different landscapes was also found by Sadri et al (2016) in the eastern United States. This confirms the findings of Laaha et al (2017), Bormann and Pinter (2017) and Li et al (2018) that the importance of local environmental elements on the process of formation of streamflow droughts is of greater importance than general global factors.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Indeed, catchment average elevation and slope were correlated to the low-flow metrics (q min , q 95 and C) (Figures 4, 5; Table 4), as reported also in previous studies (e.g. Kroll et al, 2004;Li et al, 2018;Staudinger et al, 2015).…”
Section: Relevant Catchment Characteristics For Lowflow Assessment and Predictionsupporting
confidence: 85%
“…We obtained the main catchment characteristics (climate, topography, land cover and geology) for each catchment from available data from the Federal Office of Meteorology and Climatology (MeteoSwiss) and the Federal Office of Topography (Swisstopo; Table 1). Daily gridded datasets of The 2m resolution DEM was used to calculate several topographic catchment descriptors: upslope area, exposition, slope (average slope, and fraction of area for different slope classes), average terrain roughness (1/cos(β), where β is the pixel slope; Li et al, 2018), average topographic wetness index (TWI; ln(a/tan(β), where a is the accumulated area for every pixel; Beven & Kirkby, 1979), and the drainage density (L t /A, where L t is total channel length derived from the Swiss Vector dataset-Swisstopo, and A is catchment size; Tarboton et al, 1992).…”
Section: Catchment Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Payn et al (2012) found that the impact of topographical contributing area on baseflow decreases during recession, indicating that catchment subsurface properties then gain in importance. Li et al (2017) showed that summer low flows are significantly influenced by topography in snow-dominated catchments, while Godsey et al (2014) concluded that summer low flows are strongly dependent on annual peak snow water equivalent (SWE), with a decrease leading to decreased summer low flows. Moreover, Jenicek et al (2016) showed that during high SWE years, summer low flows occur later and precipitation after maximum SWE has a significant impact on summer low flows.…”
Section: Citationmentioning
confidence: 99%